2002
DOI: 10.1046/j.1440-6047.2002.00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition problems of hospitalised children in a developing country: Thailand

Abstract: Nutritional assessment reveals the nutritional status of a patient. It thereby helps identify each patient's need for specific nutritional care and facilitates early intervention. Generally, the common nutrition and nutrition-related problems in hospitalised paediatric patients are: protein energy malnutrition in various degrees; vitamin deficiencies such as A, B1, B2, niacin, folic acid, K and E; mineral deficiencies such as Zn, Fe, Ca, Mg, P, K and Na; essential fatty acid deficiencies; carbohydrate intolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
1
11
1
2
Order By: Relevance
“…In addition, the result of the current study was found to be higher than the 37% of a study in Romania, where the geography and socio-economic status are similar to Turkey (9) and the results of studies in other developed European countries and America (7,8,19). However, the results of the current study are similar to those of Thailand (50%-60%) and lower than those of Honduras (67.3%) (20,21). The reasons for these different results can be listed as differences in patient profiles accepted for hospitalization, the methodology used in the studies, and socio-economic differences between countries and regions.…”
Section: Discussioncontrasting
confidence: 65%
“…In addition, the result of the current study was found to be higher than the 37% of a study in Romania, where the geography and socio-economic status are similar to Turkey (9) and the results of studies in other developed European countries and America (7,8,19). However, the results of the current study are similar to those of Thailand (50%-60%) and lower than those of Honduras (67.3%) (20,21). The reasons for these different results can be listed as differences in patient profiles accepted for hospitalization, the methodology used in the studies, and socio-economic differences between countries and regions.…”
Section: Discussioncontrasting
confidence: 65%
“…For instance, rates of 31.8% were seen in a Turkish study of 170 children (12). A study in Thailand found that 50–60% of hospitalized children aged 1–15 years were undernourished (13). In contrast, the prevalence of under‐nutrition in hospitalized children in developed countries is lower, with rates between 14% and 24% (3).…”
Section: Discussionmentioning
confidence: 99%
“…There is an inverse relationship between the number of patients with malnutrition and the level of development of a country [5,27,28]. In developing countries, it is known that malnutrition has been one of the primary causes of mortality in children under 5 years of age [29].…”
Section: Resultsmentioning
confidence: 99%